Current and Future Perspectives on Skin Tissue Engineering: Key Features of Biomedical Research, Translational Assessment, and Clinical Application. Issue 5 (1st February 2019) - Yu, Justine R.; Navarro, Javier; Coburn, James C.; Mahadik, Bhushan; Molnar, Joseph; Holmes, James H.; Nam, Arthur J.; Fisher, John P.
Abstract: The skin is responsible for several important physiological functions and has enormous clinical significance in wound healing. Tissue engineered substitutes may be used in patients suffering from skin injuries to support regeneration of the epidermis, dermis, or both. Skin substitutes are also gaining traction in the cosmetics and pharmaceutical industries as alternatives to animal models for product testing. Recent biomedical advances, ranging from cellular‐level therapies such as mesenchymal stem cell or growth factor delivery, to large‐scale biofabrication techniques including 3D printing, have enabled the implementation of unique strategies and novel biomaterials to recapitulate the biological, architectural, and functional complexity of native skin. This progress report highlights some of the latest approaches to skin regeneration and biofabrication using tissue engineering techniques. Current challenges in fabricating multilayered skin are addressed, and perspectives on efforts and strategies to meet those limitations are provided. Commercially available skin substitute technologies are also examined, and strategies to recapitulate native physiology, the role of regulatory agencies in supporting translation, as well as current clinical needs, are reviewed. By considering each of these perspectives while moving from bench to bedside, tissue engineering may be leveraged to create improved skin substitutes for both in vitro testing and clinical applications. Abstract : This progress report provides an overview of the latest approaches to skin regeneration using tissue engineering techniques. Current and promising future regenerative technologies are discussed from the perspectives of biomedical scientists, regulatory agencies, and clinicians. By identifying key needs and strategies, tissue engineering may be leveraged to create improved skin substitutes that bridge the gap from bench to bedside.